KNOWLEDGE MANAGEMENT PRACTICES AND PERFORMANCE IN NIGERIAN UNIVERSITIES - Ohiorenoya, John Omogeafe; Eboreime, Ohimai Friday (European Scientific Journal, ESJ, 2014)
The paper investigated if there is a relationship between knowledge management and performance and if there is variation in knowledge management effectiveness among Nigerian universities. The paper examined approved universities that have gone through Nigerian Universities Commission (NUC) accreditation process in Nigeria and selected six (6) universities which were classified into two federal universities, two state universities and two private universities based on ownership and age criteria. Random sampling and convenience sampling were used to select the various universities. These six universities had staff strength of 13,822. Questionnaires were then distributed to 389 respondents on the basis of the staff strength of each university. Correlations, and regression analysis and Analysis of Variance (ANOVA) were used to analyze the data. It was found that: variations in knowledge management practices led to differences in organizational performance; and knowledge management was effective in all universities except Benson Idahosa University; The paper recommends provision of communication facilities, full scale knowledge audit, provision of library facilities, massive training of universities’ current workforce and continuous upgrading of technology.